Influence of growth factors on Alternaria toxin(s) production and screening of ber germplasm against fruit rot resistance - and C. UMAMAHESWARI, P. NALLATHAMBI*, B.B.L. THAKORE (Indian Phytopathology, 2008)
Influence of synthetic, semi-synthetic and host extract media at different temperatures on growth of A. alternata (Fr.) Keissler and production of toxin(s) was investigated. Maximum radial growth (86mm) of the test pathogen was observed in PDA, incubated at 25o C followed by semi-selective medium (83mm) and ber fruit extract medium (75 mm). Profuse growth of mycelia (1193 mg/100ml) and crude toxin(s) production (40.1 mg/100 ml) were influenced by liquid state of semi-selective medium. Host extract (ber fruit juice) medium also favoured moderate growth (676.7 mg/100 ml) and toxin(s) production (35.93 mg/100 ml). The growth and quantity of crude toxin(s) were proportionately reduced with increase in temperatures. Inoculation of toxin(s) produced at 20 to 30o C in Czapek’s Dox, Richard’s, ber fruit juice and semi selective medium expressed yellowing and necrotic lesions, while toxins synthesized in other media showed only mild yellowing on highly susceptible host (cv. Gola). Toxin(s) produced in semi-selective medium at 25o C showed maximum infection index (56.02) followed by Richard’s (49.93) and ber fruit juice medium (36.40). Cumulative analysis of data with regard to the symptoms intensity explicated a high correlation (r = 0.90) between pathogen and toxin(s) on ber germplasm.